KADAR ASAM AMINO DANGKE DENGAN LEVEL ENZIM PAPAIN DAN LAMA PEMANASAN BERBEDA - Andi Nurul Mukhlisah; Muhammad Irfan (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this study was to look at the amino acid content of dangke made with different levels of papain enzyme and heating duration. The research consists of two stages, the first stage is the preparation of papain enzyme and the second is the determination of heating temperature and papain concentration. Dangke will be made using fresh cow's milk taken from KUNAK Bogor dairy farm. Fresh cow's milk was pasteurized at 70, 80 and 90°C respectively, then pure papain was added which has been diluted with distilled water in a ratio of 1:9. The concentration of diluted pure papain was 0.2, 0.3 and 0.4%, respectively. Salt was added at 0.4% (w/v). Dangke S3K3 treatment (90°C temperature, 0.4% papain concentration) had the highest amino acids, both non-essential and essential amino acids. This is due to the addition of papain, as it is known that amino acids are components of protein formation. The conclusion of this study is that glutamic acid is the highest amino acid in different heating treatments and concentrations. Dangke S3K3 treatment (temperature 90°C, concentration of 0.4% papain) is the highest amino acid, both non-essential amino acids and essential amino acids.